Implementasi Steganografi pada Citra Digital Menggunakan Metode Least Significant Bit (LSB) dengan Pengamanan Pesan Menggunakan Kriptografi Sederhana - Nasution, Mohammad Haykhal; Anrilva, Nura Dara; Salsabilah, Nazwa; Rizky, Shafa Adira (JIKUM: Jurnal Ilmu Komputer, 2026)
Steganography is a technique used to conceal secret information within digital media in order to prevent unauthorized parties from detecting the existence of the message. One commonly used approach is the Least Significant Bit (LSB) method due to its simplicity and high imperceptibility. However, if the hidden message is successfully extracted, the confidentiality of its content may still be at risk. Therefore, this research implements a digital image steganography system using the LSB method, in which the secret message is first encrypted using a simple encryption mechanism before the embedding process. The encrypted message is then embedded into a digital image by modifying the least significant bits of pixel values. The developed web-based application allows users to embed and extract secret messages effectively. The results show that the embedding and extraction processes are successfully performed, and the stego image does not exhibit noticeable visual differences compared to the original image. These results indicate that the proposed approach can conceal secret messages while maintaining acceptable visual quality of the image.